Experience of integrated Traditional Chinese and Western nursing for a patient undergoing endoscopic guided placement of nasointestinal ileus tube (1例内镜下经鼻肠梗阻导管放置患者的中西医护理体会) - PENG Dan (彭丹); XU Bing (许冰); TANG Ling (唐玲); YAO Na (姚娜); ZHANG Chunshuang (张春双) (中西医结合护理)
This paper summarized the nursing experience for a patient undergoing endoscopic guided placement of nasointestinal ileus tube. Key issues of nursing included preparation of insertion tube, cooperation during tube placement, psychological nursing , medication guidance, tube maintenance , nutrition care, pain control with Traditional Chinese Medicine, extended care. A comprehensive nursing of integrated Traditional Chinese and Western medicine is potentially effective to relieve the pain during placement and improve the rehabilitation of the patient. (本文总结1例内镜下放置肠梗阻导管的中西医护理体会, 包括置管的准备、置管过程中的配合以及心理护理、药物指导、管路护理、营养护理、中医疼痛干预、延续护理等针对性护理措施。通过中西医综合的护理模式进行多角度干预, 减轻患者疼痛, 改善患者临床症状, 促进康复。)